Fear of Detection and Efficacy of Prevention: Using Construal Level to Encourage Health Behaviors - Achar, Chethana; Agrawal, Nidhi; Hsieh, Meng-Hua (Journal of Marketing Research, 2020)
This research examines the psychological processes and factors that shape illness-detection versus illness-prevention health actions. Four experiments using contexts of mental health, skin cancer, and breast cancer show that illness detection evokes fear, which undermines engagement in detection behaviors. Considering detection at low (vs. high) levels of thought reduced fear and increased health persuasion. Illness prevention is driven by self-efficacy perceptions and considering prevention at high (vs. low) levels of thought increases persuasion. In further evidence of process, trait fear moderated the detection effects, and dispositional self-efficacy moderated the prevention effects. As an intervention, framing a detection action as serving illness-prevention goals increased people’s likelihood of engaging with an online breast cancer detection tool. These findings illuminate the psychology of detection as being distinct from the psychology of prevention, identify the role of fear in the consideration of health behaviors, and show contexts in which construal levels have divergent effects on health persuasion.